2022
DOI: 10.3389/fphar.2022.965661
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of dexmedetomidine and its mechanism

Abstract: Dexmedetomidine (DEX) is a highly selective α2 receptor agonist that is routinely used in the clinic for sedation and anesthesia. Recently, an increasing number of studies have shown that DEX has a protective effect against brain injury caused by traumatic brain injury (TBI), subarachnoid hemorrhage (SAH), cerebral ischemia and ischemia–reperfusion (I/R), suggesting its potential as a neuroprotective agent. Here, we summarized the neuroprotective effects of DEX in several models of neurological damage and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 113 publications
0
16
0
Order By: Relevance
“…Mechanistic studies have clearly demonstrated that DEX serves a variety of signaling pathways. When examined further, DEX is often involved in signaling pathways that are activated under oxidative stress and triggered by various stressors [ 127 ]. Additionally, what is worth mentioning are microRNAs (miRNAs), which play an important role in post-transcriptional gene regulation [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies have clearly demonstrated that DEX serves a variety of signaling pathways. When examined further, DEX is often involved in signaling pathways that are activated under oxidative stress and triggered by various stressors [ 127 ]. Additionally, what is worth mentioning are microRNAs (miRNAs), which play an important role in post-transcriptional gene regulation [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have shown that M1 type of macrophages rely on glycolysis to generate energy, while M2 type produces ATP through the tricarboxylic acid cycle [29,30], which corresponds to the pathway of energy provision under stress-and steady-state. α 2 -AR is widely distributed in central nervous system and peripheral tissues, such organ protective effects of Dex have been detected in brain [31], heart [32] and lung [33] injury. Likewise, our previous experiments found that excitation of α 2 -AR exhibits cytoprotective effects on human renal tubular epithelial cells [15] and pulmonary microvascular Endothelial cells [17] including activating intracellular focal adhesion kinase (FAK) and PI3K/Akt pathway, which increase Akt phosphorylation [18,34].…”
Section: Discussionmentioning
confidence: 99%
“…The possible neuropharmacological mechanisms of action of the rapamycin and axitinib synergy should note. Thus, rapamycin reduces the production of HIF-1α [20,21] and abolishes insulin-induced HIF-1 activation in retinal pigment epithelial cells [22]. Hence, mTOR upstream is considered a way of HIF-1α activation and HIF-1-dependent gene expression [20].…”
Section: Discussionmentioning
confidence: 99%